58.2k views
5 votes
F(x) = -5x -4 and g(x) = x^2 + 3 find (g-f)(x)

1 Answer

3 votes

ANSWER


(g-f)(x)=x^2\text{ + 5x + 7}

Step-by-step explanation

We are given that:


\begin{gathered} f(x)\text{ = -5x - 4} \\ \text{and } \\ g(x)=x^2\text{ + 3 } \end{gathered}

(g - f)(x) is the same as g(x) - f(x).

So, that is:


\begin{gathered} (g-f)(x)=g(x)-f(x)=x^2\text{ + 3 - (-5x - 4)} \\ (g-f)(x)=x^2\text{ + 3 + 5x + 4} \\ (g-f)(x)=x^2\text{ + 5x + 7} \end{gathered}

That is the answer.

User Aliona
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.